Synthesis and Characterization of Sba-15 and Cu/Sba-15 Catalysts for Photoreduction of Carbon Dioxide - Mohd Ridzuan, Azis (2012)
The greenhouse effect is a process by which thermal radiation from a planetary surface is absorbed by atmospheric greenhouse gases, and is re-radiated in all directions.The increasing concentrations of the greenhouse gases in the atmosphere, where the major contribution comes from carbon dioxide (CO2). The result from a continued increase in CO2 concentration will cause major changes in global climate .Due to high concentration of CO2 in the environment, advanced oxidation process (AOP) was proposed. AOP is a process in which the oxidative capacity of a parent compound is modified to make oxidation-reduction reactions more rapid or complete. Due to the best properties that it can retain at high themperature and thermal stability SBA-15 has been chosen as catalysts. SBA-15 and Cu supported mesoporous siliceous SBA-15catalysts have been prepared by direct synthesis methods and wetness impregnation method, respectively and are systematically characterized. The characterizations of the synthesized samples were done using Fourier Transforms Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Thermal Gravimetric analysis (TGA) and X-ray diffraction (XRD). The FTIR analysis shows that when SBA-15 was doped with copper, the % transmittance of the spectral had decreased. From the SEM analysis, the surface morphology of SBA-15 was changed from smooth to course and irregular structure due to existence of Cu in SBA-15. XRD measurement shows that the amorphous phase for pure SBA-15 was changed to crystalline phase when Cu was deposited into SBA-15 proving that Cu present in the SBA-15 structure. The TGA analysis shows that with existence of Cu in SBA-15, enhanced the thermal stability properties of catalysts. Thermo gravimetric analysis shows that the copper deposition on SBA-15 is stable up to a temperature of 515 °C and that the copper decomposes between 515 °C and 798 °C. The results of the FTIR, SEM, XRD and TGA testify completely that the Cu was incorporated into the framework sites of the SBA-15.